Matrine@chitosan-D-proline nanocapsules as antifouling agents with antibacterial properties and biofilm dispersibility in the marine environment - Hao, Xiangping; Yan, Weilu; Yang, Jingzhi; Bai, Yun; Qian, Hongchang; Lou, Yuntian; Ju, Pengfei; Zhang, Dawei (Frontiers in Microbiology, 2022)
Antifoulants are the most vital efficient in antifouling coatings to prevent the marine organism colonized on the undersea substrate surfaces. Besides the antibacterial performance, inhibiting the biofilm formation is an important criterion of the antifouling coatings. In this work, we synthesized pH-responsive matrine@chitosan-D-proline (Mat@CS-Pro) nanocapsules of about 280 nm with antibacterial properties and biofilm dispersibility. The prepared Mat@CS-Pro nanocapsules exhibited high-level antibacterial properties, reaching about 93%, 88%, and 96% for E. coli, S. aureus, and P. aeruginosa, respectively. Such nanocapsules can cause irreversible damage to bacteria and cause them to lose their intact cell structures. Moreover, Mat@CS-Pro nanocapsules also possessed outstanding dispersal biofilm performances, in which the biofilm thickness of E. coli, S. aureus, and P. aeruginosa were decreased by 33%, 74%, and 42%, respectively, after three days of incubation. Besides, the Mat@CS-Pro nanocapsules had remarkable pH-responsive properties. As the environmental pH became acidic, the nanocapsules swelled to about 475 nm and the released concentration can reach 28.5 ppm after immersion for 10 h but maintained a low releasing rate in pH 8 conditions.